Positifikasi Asketisme dalam Islam dengan Pendekatan Paradigma Klasik dan Modern - Nurkhalis Nurkhalis (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2014)
Asceticism in Islam is perceived as an ascetic (zuhd), the alienation of self and soul  to be more focus in practicing pure worship (ibadah mahdhah). It is not logical if asceticism in  Islam is synonymous with faqir (the poor) or ju'i (hungry) or distancing oneself from the  crowd and togetherness. The concentration of asceticism attempts to create goodness and  virtue, physical strength, emotion and mood. Thus, the introduction of Islamic asceticism to  zuhd is included in the historical iron cage, whereas contemporary Islamic asceticism should be  included in iron cage of modernity. Islamic asceticism is motivated by ethos and ethics that are  socio-centric, not egocentric who only wants perfection and self righteousness. The pattern of  Islamic asceticism is not stagnant zuhd but moderate zuhd as the attitude that promotes  excellence and achieves all lawful things by performing various contributions to social  salvation. Therefore, moderate zuhd equals to productive and participatory zuhd.